2019
DOI: 10.21273/jashs04625-18
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Fruit Drop in Huanglongbing-affected ‘Valencia’ Sweet Orange

Abstract: For field-grown ‘Valencia’ sweet orange (Citrus sinensis) affected by Huanglongbing [HLB (Candidatus Liberibacter asiaticus (CLas)], trees that displayed more severe HLB symptoms (severe trees) had 74% fruit drop before harvest; however, the drop rate for less symptomatic trees (mild trees) was 45%. For mature fruit (3 weeks before harvest) still attached to the branches, 60% of them from severe trees were “loose fruit” [f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Fruit drop is a major concern in HLB-affected trees (Albrigo and Stover, 2015). The preharvest fruit drop increases as the HLB symptoms increase and canopy density decreases (Tang et al, 2019). Similarly, in this study, a negative correlation between canopy volume and fruit drop was observed for the first 2 years of the study (Table 1).…”
Section: Discussionsupporting
confidence: 82%
“…Fruit drop is a major concern in HLB-affected trees (Albrigo and Stover, 2015). The preharvest fruit drop increases as the HLB symptoms increase and canopy density decreases (Tang et al, 2019). Similarly, in this study, a negative correlation between canopy volume and fruit drop was observed for the first 2 years of the study (Table 1).…”
Section: Discussionsupporting
confidence: 82%
“…The significant reduction of pre-harvest fruit drop by trunk-injected SAR inducers at 0.25 g/tree (Table 3) might be attributed to their suppressive effects on Las population growth in HLB diseased citrus trees. Excessive pre-harvest fruit drop, usually happening three to 4 months prior to harvest, is positively correlated with HLB disease severity (Tang et al 2019). Earlier work has speculated that altered balance among the plant hormones abscisic acid, auxin, ethylene, and jasmonic acid caused by Las infection played a critical role in increasing preharvest fruit drop in HLB disease trees (Martinelli et al 2012;Nehela et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Huanglongbing (HLB) is a disease of citrus causing economic loss to the citrus industry around the world (Bové, 2006; Singerman and Useche, 2016). Its causal agent, Candidatus Liberibacter asiaticus ( C Las), vectored by the Asian citrus psyllid (ACP; Diaphorina citri Kuwayama), is a phloem-limited bacterium which affects phloem dysfunction leading to starch accumulation in leaves and loss of sink growth (Achor et al, 2020; Bové, 2006), as well as eventual development of thin canopies (Tang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the specificity of the leaf level measurements (light levels, angle of radiation incidence, leaf position within the canopy), leaf-level data is difficult to extrapolate to the whole canopy. Because, HLB induces reductions in canopy density (Tang et al 2019), larger scale measures may be more indicative of changes in carbon assimilation than leaf-level measures.…”
Section: Introductionmentioning
confidence: 99%